2018
DOI: 10.1017/cem.2018.96
|View full text |Cite
|
Sign up to set email alerts
|

LO34: Does utilization of an intubation safety checklist reduce dangerous omissions during simulated resuscitation scenarios?

Abstract: Introduction: One of the most high-risk tasks regularly performed by emergency medicine (EM) physicians is airway management. Many studies identify an increase in adverse events associated with airway management outside of the operating theatre. Errors of omission are the single most common human error type. To address this risk, the checklist is becoming a common pre-intubation tool. Simulation is a safe setting in which to study the implementation of a new airway checklist. The purpose of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In all, 13 randomised controlled trials were included and their findings were reported in 16 publications [20–35]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In all, 13 randomised controlled trials were included and their findings were reported in 16 publications [20–35]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2. Two of the trials were assessed to be at overall low risk of bias [27, 33, 34], nine to have some concerns [22–26, 28–32, 35] and two were at high risk of bias [20, 21]. In the 13 instances where clarification of trial methodology or missing data was needed, seven authors responded with the required information [22, 25, 27, 29–34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations